An evaluation of arrangement and description of church records in selected parishes of Cavite towards proposing a system of classification - Dilidili, Analiza P. (2008)
Effective management of information allows fast, accurate and reliable access of records; ensures the timely destruction of inactive information and the identification and protection of vital and historically important records (NAS, 2005). The Church is one of the important organizations in the history of every community because it maintains the records of its people. Proper arrangement and description of records are essential to make the information authentic, accurate, accessible, complete and comprehensive.